2012
DOI: 10.2337/db12-0004
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations in Lipid Signaling Underlie Lipodystrophy Secondary to AGPAT2 Mutations

Abstract: Congenital generalized lipodystrophy (CGL), secondary to AGPAT2 mutation is characterized by the absence of adipocytes and development of severe insulin resistance. In the current study, we investigated the adipogenic defect associated with AGPAT2 mutations. Adipogenesis was studied in muscle-derived multipotent cells (MDMCs) isolated from vastus lateralis biopsies obtained from controls and subjects harboring AGPAT2 mutations and in 3T3-L1 preadipocytes after knockdown or overexpression of AGPAT2. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 53 publications
2
48
0
Order By: Relevance
“…The upregulation of Agpat2 in adipose tissues of Ad-mKO mice is particularly interesting, as mutations in human AGPAT2 cause type 1 BSCL ( 65 ). Importantly, Agpat2 overexpression increased PA levels in 3T3-L1 adipocytes ( 41 ), and elevated PA levels were observed in eWAT of ASKO mice ( 19 ). Human BSCL2 also forms a complex with human AGPAT2 and LPIN1 in vitro ( 20,21 ), but whether these proteins interact with each other in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of Agpat2 in adipose tissues of Ad-mKO mice is particularly interesting, as mutations in human AGPAT2 cause type 1 BSCL ( 65 ). Importantly, Agpat2 overexpression increased PA levels in 3T3-L1 adipocytes ( 41 ), and elevated PA levels were observed in eWAT of ASKO mice ( 19 ). Human BSCL2 also forms a complex with human AGPAT2 and LPIN1 in vitro ( 20,21 ), but whether these proteins interact with each other in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…3C ). Interestingly, Agpat2 , an enzyme governing the conversion of lysophosphatidic acid (LPA) to phosphatidic acid (PA ) ( 40,41 ), was the only TG synthesis pathway gene that was induced in eWAT 12 days after Bscl2 deletion (supplementary Excel fi le; Fig. 3C ).…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…It has been proposed that AGPAT2 deficiency determines inability of preadipocytes to differentiate into mature adipocytes. In fact, Subauste et al [7] showed that muscle-derived multipotent cells from CGL patients have impaired adipogenic differentiation in vitro and that pioglitazone increases the levels of terminal differentiation markers C/EBPα and PPARγ and the accumulation of lipid droplets in these cells, suggesting that AGPAT2 deficiency impairs PPARγ activation during adipogenesis [7]. The differentiation process that generates mature adipocytes from fibroblast-like preadipocytes requires the development of highly specialized cellular structures such as lipid droplets, involving massive cytoplasmic remodeling.…”
Section: -Acylglycerol-3-phosphate O-acyltransferase 2 (Agpat2)mentioning
confidence: 97%
“…However, liver adenoviral overexpression of acylglycerol-3-phosphate-O-acyltransferase 1 (AGPAT1) and AGPAT2 in Agpat2 -/-mice failed to improve liver steatosis, suggesting that lipodystrophy and insulin resistance are critical for the liver phenotype of these animals [56•]. Indeed, cellular studies have shown that AGPAT2 (but not AGPAT1) knockdown [57] in 3T3L1 cells strongly impairs adipogenesis [58]. AGPAT2 deficiency alters lipid synthesis and leads to an accumulation of lysophosphatidic acid.…”
Section: Lipid Synthesismentioning
confidence: 99%
“…AGPAT2 deficiency alters lipid synthesis and leads to an accumulation of lysophosphatidic acid. Treatment with the PPARγ agonist rosiglitazone partially restored the adipogenesis [57].…”
Section: Lipid Synthesismentioning
confidence: 99%